2006
DOI: 10.2151/sola.2006-019
|View full text |Cite
|
Sign up to set email alerts
|

Variation in PSC Occurrence Observed with ILAS-II over the Antarctic in 2003

Abstract: The Improved Limb Atmospheric Spectrometer (ILAS)-II frequently observed polar stratospheric clouds (PSCs) in the Southern Hemisphere (SH) throughout the winter of 2003. Simultaneous observations of the aerosol extinction coefficient (AEC) at 780 nm, nitric acid, and water vapor data were analyzed to investigate the ambient thermodynamic conditions associated with observed PSCs. PSCs were first observed with ILAS-II at the end of May, and observed most frequently in August/September as temperatures cooled. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
(35 reference statements)
3
7
0
Order By: Relevance
“…This study examines whether the enhanced PSC occurrence observed can be explained by gravity wave motions. It should be noted that previous work by Saitoh et al (2006) has identified a similar enhanced PSC occurrence in June 2003 compared to that identified by temperature thresholds using ILAS-II data. An enhanced level of PSC occurrence in June 2003 was also observed and modelled by Höpfner et al (2006).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…This study examines whether the enhanced PSC occurrence observed can be explained by gravity wave motions. It should be noted that previous work by Saitoh et al (2006) has identified a similar enhanced PSC occurrence in June 2003 compared to that identified by temperature thresholds using ILAS-II data. An enhanced level of PSC occurrence in June 2003 was also observed and modelled by Höpfner et al (2006).…”
Section: Resultssupporting
confidence: 68%
“…This is a strong validation of the results presented in this study since Saitoh et al (2006) uses the mean plus five standard deviations from the ILAS-II aerosol extinction data to identify PSC, an extremely conservative threshold.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…In the troposphere and stratosphere, it plays an important role in the radiation balance of the earth (e.g., Forster and Shine, 1999;Solomon et al, 2010), and it influences atmospheric chemistry via its product, the hydroxyl radical (OH) (Stenke and Grewe, 2005), and via polar stratospheric clouds (PSCs) (Saitoh et al, 2006).…”
Section: Introductionmentioning
confidence: 99%